Power Scavenging Microsystem for Smart Contact Lenses - Pourshaban, Erfan; Karkhanis, Mohit U.; Deshpande, Adwait; Banerjee, Aishwaryadev; Hasan, Md Rabiul; Nikeghbal, Amirali; Ghosh, Chayanjit; Kim, Hanseup; Mastrangelo, Carlos H. (Small (Weinheim an der Bergstrasse, Germany), 2024)
On‐the‐eye microsystems such as smart contacts for vision correction, health monitoring, drug delivery, and displaying information represent a new emerging class of low‐profile (≤ 1 mm) wireless microsystems that conform to the curvature of the eyeball surface. The implementation of suitable low‐profile power sources for eye‐based microsystems on curved substrates is a major technical challenge addressed in this paper. The fabrication and characterization of a hybrid energy generation unit composed of a flexible silicon solar cell and eye‐blinking activated Mg–O2 metal–air harvester capable of sustainably supplying electrical power to smart ocular devices are reported. The encapsulated photovoltaic device provides a DC output with a power density of 42.4 µW cm−2 and 2.5 mW cm−2 under indoor and outdoor lighting conditions, respectively. The eye‐blinking activated Mg–air harvester delivers pulsed power output with a maximum power density of 1.3 mW cm−2. A power management circuit with an integrated 11 mF supercapacitor is used to convert the harvesters’ pulsed voltages to DC, boost up the voltages, and continuously deliver ≈150 µW at a stable 3.3 V DC output. Uniquely, in contrast to wireless power transfer, the power pack continuously generates electric power and does not require any type of external accessories for operation. A hybrid energy generator composed of a flexible silicon solar cell and eye‐blinking activated Mg–O2 harvester is reported. A power pack containing these generators continuously deliver ∼150 µW at a stable 3.3 V DC. Unlike wireless power transfer, the power pack continuously generates electric power and does not require any type of external accessories for operation.